Time triggered handoff schemes in cognitive radio networks: A survey. (15th January 2018) - Mir, Usama; Bhatti, Zeeshan Ahmed
Abstract: Rapid development in wireless networks has largely raised the demand for spectrum bandwidth. However, current static spectrum allocation policy is unable to meet this ever-growing requirement which causes the spectrum scarcity problem. Cognitive radio network (CRN) has emerged as a grasping solution to scarcity problem where the secondary or unlicensed users are allowed to access the temporary free channels owned by the licensed or primary users. Among other important steps involved in a spectrum management process, handoff plays an essential role since it requires shifting the on-going transmission of a secondary user (SU) to a free channel without degrading the quality of service. An extensive work has been done in the field of spectrum handoff for CRNs. This work is mostly classified in timing, probability, and operating mode based handoff schemes. In this paper, we present a detailed classification and a compressive survey for time triggered handoff schemes. This topic is chosen because in time triggered handoff process, the handoff decision needs to be performed based on continuously sensing the arrival and departure patterns of licensed users, thus making it an important area of research. Therefore, we discuss the pros and cons for time triggered handoff schemes in detail.